Enhancement of network lifetime of cloud-assisted internet of things: new contribution of deer hunting and particle swarm optimisation. (24th February 2021) - Alameen, Abdalla; Gupta, Ashu
In general, WSN maintains the chief support of cloud-assisted internet of things (CIoT). This paper intends to implement a WSN-assisted CIoT model which involves two processes: one is optimal cluster head selection, and the other is optimal shortest path selection. The main intent of this optimal cluster head selection is to select a cluster head using a hybrid optimisation algorithm with the objective of minimising the distance between each IoT sensor node and cluster head and consumed energy. Moreover, the same hybrid algorithm is used in the optimal shortest path selection process. The beneficial concepts of two well-performing meta-heuristic algorithms like deer hunting optimisation algorithm (DHOA), and particle swarm optimisation (PSO) are merged to frame a hybrid algorithm termed as particle swarm-based deer hunting optimisation algorithm (PS-DHOA) to be suited for both cluster head selection and route selection. Developed model has been validated through effective performance analysis.